Role of NLRP3 Inflammasome in Rheumatoid Arthritis - Yin, Hui; Liu, Na; Sigdel, Keshav Raj; Duan, Lihua (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by multi-articular, symmetrical and invasive arthritis resulting from immune system abnormalities involving T and B lymphocytes. Although significant progress has been made in the understanding of RA pathogenesis, the underlying mechanisms are not fully understood. Recent studies suggest that NLRP3 inflammasome, a regulator of inflammation, might play an important role in the development of RA. There have been increasing clinical and pre-clinical evidence showing the treatment of NLRP3/IL-1β in inflammatory diseases. To provide a foundation for the development of therapeutic strategies, we will briefly summarize the roles of NLRP3 inflammasome in RA and explore its potential clinical treatment.